PERAN KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIDIKAN - Muhammad Munawir Pohan (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Since the enactment of decentralization of education, maximizing the role of school and community stakeholders has become very important in supporting the success of the education process in schools. The actualization form of education decentralization is realized by the existence of school committees which are expected to carry out their roles maximally in improving the quality of education. With the aspect seen, namely the role of the school committee as consideration, support, control, and role as mediator, the role is as a form of improving the quality of education in accordance with the mandate stated in the Minister of National Education Decree Number: 044 / U / 2002 dated April 2, 2002 Therefore, with regard to efforts to improve the quality of education, the government has actually issued a policy namely education autonomy. Educational autonomy as a form of education decentralization, gave birth to an important concept for the implementation of education. One of these important concepts is School-Based Management (SBM) which later gave birth to the School Committee as a manifestation of community participation in the world of education. The concept encourages school and community committees to become unified and complementary, and can even provide a color for the formulation of quality in schools. Society is an unequaled educational resource for education units. In community schools can be a foundation for improving and service quality education in the implementation of education.